Floral torans hanging on the door of a Koli home - Mumbai Archive Project Team (Jio Institute, 2024)
During festivals and weddings, people make traditional floral torans from marigolds and mango leaves. People hang torans from doorways to welcome the goddess of wealth, Lakshmi, into their household.